Optic synapses are found in diencephalic neuropils before development of the tectum in Xenopus. - Gaze, R; Wilson, M; Taylor, J (Springer-Verlag, 1993)
The position of the earliest optic synapses in Xenopus and the stage at which they developed were studied with the electron microscope after labelling of optic axons with horseradish peroxidase. In addition, tritiated thymidine autoradiography and bromodeoxyuridine immunohistology were used to identify the birth dates of cells in the regions where the synapses had been found. The earliest mature optic synapses were found in the mid-diencephalic region, where the major diencephalic optic neuropils were beginning to develop. These synapses were seen at stage 35/36, before cells in the tectal precursor region had become postmitotic. In other animals labelling with tritiated thymidine or bromodeoxyuridine showed that cells in the diencephalon, close to where the synapses had been seen, were becoming postmitotic at the time the earliest optic axons arrived. The first optic synapses to form in the developing Xenopus visual system thus appeared to do so in the neuropil of Bellonci and the rostral visual nucleus.